2022
DOI: 10.1136/bmjopen-2021-052832
|View full text |Cite
|
Sign up to set email alerts
|

NHS Health Check programme: a rapid review update

Abstract: ObjectiveTo update a rapid review published in 2017, which evaluated the NHS Health Check programme.MethodsAn enlarged body of evidence was used to readdress six research objectives from a rapid review published in 2017, relating to the uptake, patient experiences and effectiveness of the NHS Health Check programme. Data sources included MEDLINE, PubMed, Embase, Health Management Information Consortium (HMIC), Cumulative Index of Nursing and Allied Health Literature (CINAHL), Global Health, PsycINFO, the Cochr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…However, participation in the screening procedures may be less in some categories (e.g. men, younger individuals, people with lower socioeconomic backgrounds) than in others [59]. In the USA, the US Preventive Services Task Force suggests screening for hypertension in adults aged 18 years or older [60].…”
Section: Definition Of Hypertension and Bp Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, participation in the screening procedures may be less in some categories (e.g. men, younger individuals, people with lower socioeconomic backgrounds) than in others [59]. In the USA, the US Preventive Services Task Force suggests screening for hypertension in adults aged 18 years or older [60].…”
Section: Definition Of Hypertension and Bp Classificationmentioning
confidence: 99%
“…Despite limited evidence on the optimal frequency of screening, they recommend yearly screening in adults 40 years old and in those at increased risk for developing hypertension such as blacks, individuals with high-normal BP and people who are overweight or obese [60]. Opportunistic BP measurements are now also encouraged in several countries [59] and have been recently supported in USA by the increased detection, treatment and control of hypertension associated with BP measurements in barber shops or by pharmacists [61]. Based on the available evidence, we recommend opportunistic screening for hypertension in all adults (i.e.…”
Section: Screening Versus Case Finding In the Detection Of Hypertensionmentioning
confidence: 99%
“…Despite herein discussed limitations of NHS-HC targeted screening programme, analytic investigation of its effectiveness between 2013-2017 showed improved detection of T2DM in attendees than in no attendees, see Figure 1. Those findings suggest that after further reduction of above-mentioned limitations in line with expanding scope of the programme for younger population these outcomes might be further improved in the future [21]. Second existent universal awareness programme in the UK is the NHS Diabetes scheme.…”
Section: • Stigma On Confidentiality and Privacymentioning
confidence: 95%
“…A review of almost 100 studies from 2009 to 2019 for Public Health England found that most of those that looked at sex differences concluded that men were less likely to attend. 2 It seems clear, therefore, that men of working age (under 65 years) are making less use of general practice than women. Previous research, albeit using data from 2010, has additionally shown that the difference cannot be accounted for by women attending for reproductive issues; even if these are taken into account, men of working age are still significantly less likely to attend (Figure 1).…”
Section: Uk Datamentioning
confidence: 99%
“…Health checks aim to detect risk factors for heart disease, diabetes, kidney disease and stroke. A review of almost 100 studies from 2009 to 2019 for Public Health England found that most of those that looked at sex differences concluded that men were less likely to attend 2 …”
Section: Uk Datamentioning
confidence: 99%